1988
DOI: 10.1002/j.1460-2075.1988.tb03128.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal relationship between inositol polyphosphate formation and increases in cytosolic Ca2+ in quiescent 3T3 cells stimulated by platelet-derived growth factor, bombesin and vasopressin.

Abstract: We determined the temporal relationship between the formation of inositol phosphates and increase in cytosolic [Ca2+] elicited by bombesin, vasopressin and platelet‐derived growth factor (PDGF) in quiescent Swiss 3T3 cells. These responses were measured under identical conditions. Bombesin caused a rapid increase in inositol 1,4,5‐trisphosphate which coincided with the increase in cytosolic [Ca2+]. This was followed by a slower but marked increase in inositol 1,3,4‐trisphosphate and inositol‐bisphosphate. Vaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(48 citation statements)
references
References 47 publications
3
44
1
Order By: Relevance
“…One is from bombesin or thrombin, and the other is from PDGF. The former is disrupted by pertussis toxin, which suggests the involvement of a G protein, and the latter is insensitive to the toxin (26)(27)(28)(29)(30)(31). Our results presented in Fig.…”
Section: Discussionsupporting
confidence: 49%
“…One is from bombesin or thrombin, and the other is from PDGF. The former is disrupted by pertussis toxin, which suggests the involvement of a G protein, and the latter is insensitive to the toxin (26)(27)(28)(29)(30)(31). Our results presented in Fig.…”
Section: Discussionsupporting
confidence: 49%
“…PLC␤ produces inositol 1,4,5-triphosphate which mobilizes Ca 2ϩ from internal VOL. 21,2001 EFFECTS OF NEUROPEPTIDES ON PROSTATE CANCER CELL LINEstores and diacylglycerol which in turn, activates PKC (23,35,59). A recent study by Buhl et al showed that G␣12 is also activated by bombesin (18).…”
Section: Discussionmentioning
confidence: 99%
“…Excess Fura-2/AM was removed by washing with HBSS. Intracellular calcium measurements were carried out using 2 ml of cell suspension at 37 Њ C within 2 h of loading as described earlier (27,28). Briefly, the fluorescence was monitored in a luminescence spectrometer (LS-5; Perkin-Elmer, Norwalk, CT) with an excitation wavelength of 336 nm and an emission wavelength of 510 nm using leptin (1 nmol и liter .…”
Section: Methodsmentioning
confidence: 99%